The effect of Larinus maculates F. Cocoon Aqueous Extract in Some Immunological Aspects of Male Albino Mice - Alasady, Zainab Thamer; Al-Shmgania, Hanady S. A.; Jwad, Muna Shukri Mahmod (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Traditional folk medicine is applied in the treatment of diversity chronic and acute conditions all over the worlds.  This study was carried out to assess the capability of aqueous beetle cocoon extract (Lorinus maculates F.) commonly known as (Tihan) in stimulating immune  response. Adult mice (5 in each group) were divided into two groups: the first one orally administered with 150 mg/kg and the second group received normal saline as a control group for 14 days. Bone marrow and spleen were proceed for mitotic index and phagocytosis estimated. The results showed a significant increase in mitotic index and phagocytosis in treaded mice in comparing with the negative control. These results concluded that Tihan has a potential role in innate immune response.